AB0186 Benchmarking Disability with The HAQ-Di. A New Normogram in A Latin American Non-Rheumatic Population. (15th July 2016) - Espinosa-Ortega, F.; Enriquez-Antonio, O.; Arce-Salinas, C.A.; Ruiz-Medrano, E.; ,
Abstract : Background: The HAQ-Di is broadly used to measure functional disability in RA, and other rheumatic diseases. It can not differentiate disability caused by arthritis or that caused by other illnesses. Whether non-modifiable constitutional factors (e.g. age), personal behaviors, or common comorbidities exert influence over disability measurement, has only been assessed in quite few trials. Objectives: We aimed to determine disability values in a population without previous musculoskeletal conditions, and recognize its main determinants. Methods: Our Hospital ambulatory area offer primary care attention over thirty thousand people. HAQ-Di was ask to be filled by 1, 000 patients of a an annual check-up program, and other primary care areas. Were evaluated those older than 18 years and younger than 95 who signed informed consent; participants with any previous rheumatic disease, and chronic pain condition were excluded. Demographic variables, as well as formal education, health behaviors (smoking and exercise), and comorbidities (Charlson index) were recorded. Bivariate correlations by Spearman, and Kruskall Wallis or t-tests were performed as appropriate. We considered p<0.05 as statistically significant value. Results: Nine hundred and seventy eight patients were enrolled (22 rejected), their mean age was 56.5±14.6 years, 38% were female, mean BMI was 27.5±4.7 kg/m 2, and a Charlson's score of 1.15±1.9. HAQ-Di population mean was 0.21±0.51 with 29% of the respondents had some kind of disability (HAQ-Di value >0.0). Accordingly to the normogram, disability increased with age (figure 1 ) (r =0.4; p<0.000). Higher HAQ-Di scores were also related with female gender (women 0.307±0.596 vs. men 0.137±0.385; p<0.001); higher Charlson score (r=0.435; p<0.001); lower formal education (rs=0.41, p<0.001; from 0.723±0.847 in group with only 6 years of instruction to 0.078±0.230 in postgraduate group); and no or mild physical activities (rs=-0.320, p<0.001; from HAQ-Di of 0.489±0.724 in the lowest fitness group to 0.118±0.370 in higher exercise group). We could not find influence in disability by smoking status or BMI. Moreover, those with diabetes mellitus (DM) or high blood pressure (HBP) disclosed higher disability (with DM 0.434±0.7 vs. without DM 0.113±0.329, p=0.005, and with HBP 0.445±0.703 vs. without HBP 0.092±0.278; p=0.001) Conclusions: Almost one third of our non-rheumatic population has some kind of functional disability. Although It seems to appear as an aging phenomenon in the general population, might be influenced by comorbidities, healthy behaviours, and sociocultural factors. Thus, these variations must be taken into account when HAQ-Di is used in patients with rheumatic conditions, particularly RA, where HAQ-Di is frequently used in the making decision process. References: Krishnan E et al. Normative values for the Health Assessment Questionnaire. Arthritis Rheum 2004;60(3):953–960. Fries JF et al. Measurement of patient Outcomes in arthritis, Arthritis and Rheumatism, 1980;23, 137–145. Bruce B et al. The Health Assessment Questionnaire, Clin Exp Rheumatol 2005; 23 (Suppl. 39): S14-S18. Disclosure of Interest: None declared